Republic of Mozambique Joint World Bank-IMF Debt Sustainability Analysis - IDA; IMF (International Development Association (IDA) and the International Monetary Fund (IMF), 2020)
Mozambique’s debt remains in distress, which is unchanged from the previous DSA published in June 2019. Consideringthat, to a large extent, future borrowingand governmentguarantees reflect state participation in the sizable liquified natural gas (LNG) development, debt is deemed sustainable in a forward-looking sense. Participation in the recently announced G20 initiative would provide debt service relief in the near term, thus flattening the projected sharp deterioration in debt liquidity indicators due to the COVID-19 pandemic. The possibility of an extension of the G20 initiative into 2021 would be a further mitigating factor for the debt sustainability assessment. The present value (PV) of external public and publicly guaranteed (PPG) debt relative to GDP is projected to remain above the prudent threshold with a gradual declining path dropping below the threshold by 2028.The PV of PPG external debt relative to exports would drop below the prudent threshold in 2024. The ratio of external public debt service to fiscal revenues would drop below the prudent threshold temporarily in 2020 but would breach again the threshold until 2030. The debt service-to-exports ratio would remain around the prudent threshold until 2023, when it drops and remains below the threshold for the rest of the projection period.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; economic development / desenvolvimento económico

The Evidence Is In: How Should Youth Employment Programs In Low-Income Countries Be Designed? - Fox, Louise; Kaul, Upaasna (Policy Research Working Papers, 2018)
Youth in many low-income countries are entering the labor force in unprecedented numbers, yet many struggle to secure rewarding livelihoods. This paper outlines the economic development challenges that constrain youth's transition into employment, and it parses the evidence on which programs and policies appear to speed that transition. It concludes that it may be time for a fundamental reassessment of approaches for addressing youth employment and the youth transition in low-income countries. Employment opportunities in low-income countries reflect the pace of economic and structural transformation. In designing strategies, policies, and programs to meet the entry-into-employment challenge for youth, the starting point is to diagnose the economy and current/future employment opportunities. Combined with the analysis of youth employment problems from a structural transformation perspective, evidence from rigorous evaluations of youth employment interventions provides new insight into which kinds of interventions are more likely to help youth succeed in certain contexts. The evidence reviewed here casts serious doubt on the efficacy and value of training interventions to help youth enter formal wage employment. The case is stronger for interventions that speed the transition to self-employment in farming or non-farm household enterprises. Support for development of transferable character skills and social integration among youth through positive youth development programs should be tested further for employment and earnings impacts, perhaps along with cash transfers to youth or access to finance. In reviewing the evidence on the cost-effectiveness and sustainability of youth employment impacts, the paper also notes the need for better measures of displacement and general equilibrium effects.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; employment / emprego; youth / juventude

Poverty and Well-Being in Mozambique: Fourth National Poverty Assessment - Ministry of Economics and Finance (Ministry of Economics and Finance - Directorate of Economic and Financial Studies, 2016)
This report provides a comprehensive analysis of poverty and well-being, including temporal trends, in Mozambique. It is based on the 2014/15 household budget survey data (Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15), conducted by the National Statistics Institute (Instituto Nacional de Estatística, INE). Results from this latest survey are compared to those obtained in previous survey rounds (2008/09, 2002/03 and 1996/97). We consider poverty and well-being across an array of dimensions and using two principal approaches. The first approach focuses on consumption allowing assessment of progress towards the Millennium Development Goals. The second principal approach relies on multidimensional methods for assessing poverty and well-being. The indicators employed are drawn from the four household budget surveys. They relate to education, health, housing, and possession of durable goods.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; economic development / desenvolvimento económico; poverty / pobreza

Natural Gas and Socio-Economic Transformation in Mozambique: Some Preliminary Evidence - Uetela, Pedro; Obeng-Odoom, Franklin (The Journal of Energy and Development, 2015)
The aim of this article is to extend the state of analysis on the impacts of gas development in Mozambique by evaluating the relationship between the gas sector, the Mozambican economy, and social change. As the resource curse framework is only limited to economic growth, this work utilizes two alternative frameworks—the Staples approach and the Linkages approach—that are melded into an institutional analysis, looking simultaneously at “benefits, costs, and uncertainties” or “blessings, uncertainties, and curses,” and used to conceptualize progress more widely to include not only growth, but other externalities and broader social change as applied to the case of Mozambique. In so doing, the evidence suggests that the natural gas industry in Mozambique has contributed to both the expansion in economic growth and social change. However, the positive experience with social change arises from direct intervention and not necessarily the result of the related economic growth. Indeed, in the process of economic growth, the production and export of natural gas in Mozambique have raised the possibility of major socio-economic and ecological dangers. Contrary to the theoretical criticism of spending windfall revenues on social services as wasteful, we argue that only strategic social and ecological expenditures of gas revenues can provide and increase the chances of the gas industry becoming transformational economically, socially, and ecologically. The article is organized as follows; the next section deals with conceptualizing the paper and describing the sources of data. This is followed by sections that present the results, a discussion of those results, and conclusions and policy implications from the study.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; ⛔ No DOI found

The Importance of Microfinance for Development of MSMEs in ASEAN: Evidence from Indonesia - Tambunan, Tulus (Journal of ASEAN Studies, 2014)
Despite studies on microfinance (MF) or development of microfinance institutions (MFIs) in Asia developing countries, including countries as member states of the Association of Southeast Asian Nation (ASEAN), are growing, not so much attention have been given to the role of MF in financing micro, small and medium enterprises (MSMEs). Based on a key literaturestudy and analysis of secondary/national data, the main aim of this study is to fill this gap. It shows that in many ASEAN member states (AMS) MF has developed to some significant degree, although the rate of growth (e.g. number of MFIs, number of depositors and debtors, total loans allocated, etc.) as well as the market structure of MF vary across member states. From the Indonesian case this study comes with two most interesting facts. First, majority of MSMEs do not have access to credit from banks and/or other formal non-bank financial institutions. Second, MF services or MFIs are growing fast, and the most popular MF program so far is Kredit Usaha Rakyat (KUR), or people business credit (i.e. a credit scheme without collateral), introduced during the SBY period
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico

Country Review Report: Republic of Mozambique - African Peer Review Mechanism (African Peer Review Mechanism, 2009)
The report is divided into seven chapters. This introductory chapter is followed by Chapter Two, which provides an overview of Mozambique as a backdrop to the report. Chapters Three to Six evaluate developments and challenges in the four APRM focus areas (Democracy and Political Governance; Economic Governance and Management; Corporate Governance; and Socio-Economic Development) respectively. Each of these chapters has two sections: the first analyses the codes and standards of the APRM, while the second assesses the APRM‘s objectives for that thematic area. Each section begins with a summary of the CSAR, followed by the findings of the CRM and, finally, the APR Panel‘s recommendations on the identified challenges. Effort has also been made to highlight areas of best practice in boxes. Chapter Seven discusses the cross-cutting issues considered critical due to their wider impact on governance and thus require holistic, immediate and urgent attention. These salient issues are the following: Poverty and Inequality; Party/government/business dichotomy; Land; High levels of illiteracy; Eliminating aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. The Chapter also highlights three special issues of interest to Mozambique and the Mission - the Environment, land mines and Beira city. The NPOA received from Mozambique and the comments of the government are annexed to the report, as mandated by the APRM rules.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; governance / governação

The Indonesian Financial Crisis: From Banking Crisis to Financial Sector Reforms, 1997-2000 - Sharma, Shalendra D. (Cornell University Press, 2001)
In mid-1998, a World Bank study grimly noted that "Indonesia is in deep economic crisis. A country that achieved decades of rapid growth, stability, and poverty reduction is now near economic collapse . . . no country in recent history, let alone one the size of Indonesia, has ever suffered such a dramatic reversal of fortune." There is bitter irony in Indonesia's fall from grace. Long hailed as a model of successful economic development, it was widely predicted to escape the fate of Thailand. Between June-August 1997, as Thailand's economy unraveled and the virulent Asian flu sent shock waves through the region, the Indonesian economy remained relatively stable—a veritable rock in the stormy sea. Even the World Bank remained upbeat about the short-term outlook, believing that a widening of the intervention band would be sufficient to ward off contagion.4 The Indonesian government, which received much praise for its swift and decisive response to the crisis, went to great lengths to assure jittery investors "that Indonesia was not Thailand." Then the unthinkable happened. Indonesia suddenly succumbed to the contagion, and, measured by the magnitude of currency depreciation and contraction of economic activity, it emerged as the most serious casualty of Asia's financial crisis. What happened? Why did Indonesia (and the other high-performing Asian economies) collapse like hollow dominoes? In the numerous post-mortems that have followed, analysts have identified a number of related factors behind the region's dramatic reversal of fortune. In the case of Indonesia, the variable that soon acquired particular salience was "crony capitalism." Initially popularized by the Economist, the term quickly took a life of its own. Soon thereafter, the distinguished MIT economist, Paul Krugman, would argue that crony capitalism lay the root of Indonesia's—and indeed, East Asia's—financial woes. Krugman describes the innerworkings and manifestations of the insidious crony capitalism in evocative prose.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico